Automatic Leveling And Loading Platform For Autonomous Production Line - Baštán, Ondřej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
The following text aims to familiarize readers with the basic concepts and construction solutions of an autonomous production line using additive production to serve as a data source for research and development of industrial production systems and predictive maintenance systems. The first part deals with the conceptual arrangement of the modular autonomous production line and its components. Subsequently, the technical and construction design of the automatic platform of the autonomous 3D printer cell is described, which ensures the manipulation of the glass plate, which serves as a base-plate for the printed product.
Keywords: 3D printer; leveling; automatic production; heated bed; digitalization; automatic loader; MES; 3D farm; customized manufacturing; autonomous production cell; data collection; predictive maintenance